2022
DOI: 10.1002/smll.202106012
|View full text |Cite
|
Sign up to set email alerts
|

Oxygen Vacancy and Core–Shell Heterojunction Engineering of Anemone‐Like CoP@CoOOH Bifunctional Electrocatalyst for Efficient Overall Water Splitting

Abstract: Synthesizing cost-efficient and robust bifunctional electrocatalysts for both neutral and alkaline water splitting is highly desired, but still remains a great challenge due to the sluggish hydrogen/oxygen evolution reaction (HER/OER) kinetics. Currently, noble Pt, Ru, and Ir-based catalysts are the most efficient ones, but their high cost and scarcity greatly restrict their broad applications. [2] Therefore, enormous efforts have been made toward developing suitable and cheaper catalysts with earthabundant ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
85
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 118 publications
(87 citation statements)
references
References 64 publications
2
85
0
Order By: Relevance
“…Generally, the heterostructure with a strong interfacial interaction can trigger electron redistribution within the heterointerfaces and consequently modulate the electronic structure and optimize the adsorption energy of intermediates, and even endow the synergistic effect, providing an effective tactic to enhance the intrinsic activity of the active sites. , For instance, the pea-like heterostructured CoP–Mo 2 C incorporated in the N-doped carbon displays a strong synergy and a superior electrocatalytic HER activity . Li and co-workers recently realized the anemone-like oxygen-vacancy-enriched CoP@CoOOH core–shell heterojunction on a carbon paper, exhibiting excellent HER catalytic ability under alkaline and neutral conditions due to the core–shell synergistic effect . Also, other different components, such as Co 3 O 4 , Ni 2 P, and Co 2 P/Co, have also been integrated with CoP to fabricate efficient heterostructured electrocatalysts with advanced electronic structure and electron transport ability. However, these TMP-based materials are usually synthesized according to complicated growth–phosphorization–modification, growth–secondary growth–phosphorization strategy, or tough hybrid precursor synthesis .…”
Section: Introductionmentioning
confidence: 99%
“…Generally, the heterostructure with a strong interfacial interaction can trigger electron redistribution within the heterointerfaces and consequently modulate the electronic structure and optimize the adsorption energy of intermediates, and even endow the synergistic effect, providing an effective tactic to enhance the intrinsic activity of the active sites. , For instance, the pea-like heterostructured CoP–Mo 2 C incorporated in the N-doped carbon displays a strong synergy and a superior electrocatalytic HER activity . Li and co-workers recently realized the anemone-like oxygen-vacancy-enriched CoP@CoOOH core–shell heterojunction on a carbon paper, exhibiting excellent HER catalytic ability under alkaline and neutral conditions due to the core–shell synergistic effect . Also, other different components, such as Co 3 O 4 , Ni 2 P, and Co 2 P/Co, have also been integrated with CoP to fabricate efficient heterostructured electrocatalysts with advanced electronic structure and electron transport ability. However, these TMP-based materials are usually synthesized according to complicated growth–phosphorization–modification, growth–secondary growth–phosphorization strategy, or tough hybrid precursor synthesis .…”
Section: Introductionmentioning
confidence: 99%
“…However, it still faces a major challenge, that is, the oxygen evolution reaction (OER) with a four‐electron process (4OH – → O 2 + 2H 2 O + 4e – in an alkaline medium) results in a large overpotential and slow kinetics. [ 1,2 ] Thus, it seriously hinders its large‐scale practical application. So, designing a stable, highly active, and inexpensive electrocatalysts is a key challenge to date.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, resource consumption and environmental pollution have seriously hindered sustainable development. As a new energy source, hydrogen has the advantages of being clean and environmentally friendly with a high calorific value of combustion. Electrochemical water splitting has received a lot of attention as an ideal technology for the preparation of hydrogen energy. Although Pt/C and RuO 2 have relatively excellent properties, their low earth reserves and extravagant cost greatly impede their large-scale utilization. Therefore, the development of high-efficiency catalysts with abundant reserves and moderate price is of great application value but highly challenging. Numerous studies have demonstrated that transition metal compounds, such as nitrides, , selenides, , sulfides, , oxides/hydroxides, , and phosphides, show great promise in the field of electrocatalysis due to their high hydrogen evolution reaction (HER) and oxygen evolution reaction (OER) performances. In particular, transition metal phosphides (TMPs) are the preferred alternative to noble metals due to their low prices, adjustable valence states, and their ability to improve the adsorption–desorption behavior of the H atoms on material surfaces for high electrocatalytic performance. In particular, bimetallic phosphide electrocatalysts tend to show better electrochemical activity than monometallic phosphides owing to the strong synergy between the individual components, thus attracting more widespread interest. Unfortunately, during the electrochemical water-splitting process, the sluggish OER and HER involve different multistep reaction paths and require high activation and dissociation energies of reaction intermediates, thus demanding a catalyst with high performance .…”
Section: Introductionmentioning
confidence: 99%